A Study on the Perception of Contractors on the Implementation of Social Impact Assessment - Yusri, Nurul Hazwani; Seow, Ta Wee (Research in Management of Technology and Business, 2024)
The aim of the Social Impact Assessment (SIA) is to guarantee that the construction project will be safe and conform to accepted practice. But to ensure that the objectives of this SIA are achieved, contractors must be informed of how important this SIA is to the work they do to build the project. Therefore, three objectives—the contractor’s perspective, SIA implementation factors, and strategies to improve the perception of SIA among contractors—were developed to determine the contractor’s level of understanding of SIA. The majority of contractors believe that SIA should be adopted because it will benefit the construction industry, according to the first goal. Next, regarding the factors of SIA implementation, the contractor stated that, in addition to improving the sustainability of the project, the implementation of SIA can help the community in fostering a better relationship between the contractor and the community. The majority of respondents to the third objective—increasing contractors’ perception of SIA—said that the government should include SIA in the construction code and offer more incentives to businesses that need it. This will help in educating construction partners about the value of SIA in construction projects. As a suggestion, training and incentives are crucial inpromoting contractor involvement in SIA. This is to ensure that the contractor is more open to the interests of SIA while giving them an advantage as well.